Adsorption of mixed cationic-non-ionic surfactants at the air/water interface - Penfold, J; Staples, E; Cummins, P; Tucker, I; Thompson, L; Thomas, R; Simister, E; Lu, JR (1996)
Specular neutron reflection, in combination with hydrogen/deuterium isotopic substitution, has been used to investigate the adsorption of the mixed cationic-non-ionic surfactants hexadecyltrimethyl ammonium bromide, C16TAB,-hexaethylene glycol monododecyl ether, C12E6, at the air/water interface. Measurements were made at surfactant concentrations from below to above the critical micellar concentration, c.m.c., of the mixtures. For the C16TAB-C12E6 mixture, ideal mixing is observed at concentrations above the c.m.c. of the mixture whereas, below the c.m.c., departure from ideal mixing can be observed. The effects of temperature on the adsorption of the C16TAB-C12E6 mixture at the air/water interface are described. The total adsorption decreases with increasing temperature and the surface becomes richer in the non-ionic component of the mixture.